Peran Perempuan Anggota Badan Permusyawaratan Desa dalam Memperjuangkan Aspirasi Perempuan Tahun 2020 (Studi Perbandingan Desa Sindanglaya-Lebak dan Desa Hiliweto-Nias) - Febriyanti Valeria Roito; Zebua Zebua (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2022)
This article describes the role of women members of the BPD (Village Consultative Body) in fighting for women's aspirations by taking case studies on female BPD members in Sindanglaya-Lebak Village and Hiliweto-Nias Village. The interests of women are sometimes still ignored and women do not have the space to convey their aspirations related to their needs, this is due to the social culture of the village community which considers women to only move to take care of the private sphere and do not have rights to a more general reach in society. The role of women who are placed in a strategic position, namely the BPD, can be present to fight for the interests of village women. This research was conducted using a qualitative approach. The collected data were analyzed using descriptive analysis. The results showed that the involvement and influence of female BPD members in Sindanglaya and Hiliweto villages had almost the same influence, such as in planning and participation in decision making, female BPD members were given the same opportunity to convey suggestions and decisions in BPD internal meetings and can convey their aspirations directly to the chairman of the meeting to channel the aspirations and interests of women so that they can be realized. The aspirations and interests of women in the village of Sindanglaya have been realized one by one, starting from the development of the posyandu and its equipment, to the provision of assistance to the Sindanglaya farmer group (KWT). In Hiliweto village, too, the aspirations and aspirations of women to be actively involved as village administrators have been realized by opening access to women as widely as possible.